Immunomodulatory properties of Olea europaea leaf extract in intestinal inflammation. Issue 10 (29th August 2017) - Vezza, Teresa; Algieri, Francesca; Rodríguez‐Nogales, Alba; Garrido‐Mesa, José; Utrilla, M Pilar; Talhaoui, Nassima; Gómez‐Caravaca, Ana María; Segura‐Carretero, Antonio; Rodríguez‐Cabezas, M Elena; Monteleone, Giovanni; Gálvez, Julio
Abstract : Scope: Extracts from olive ( Olea europaea ) leaves are used in Mediterranean traditional medicine as anti‐inflammatory agents. They contain antioxidant phenolic compounds, such as oleuropeoside, which could be interesting for the treatment of inflammatory conditions associated with oxidative stress in humans, including inflammatory bowel disease. Methods and results: The anti‐inflammatory effects of olive leaf extract (0.5–25 mg/kg) were studied in two mice models of colitis (DSS and DNBS). Olive leaf extract (0.1–100 μg/mL) immunomodulatory effects were also investigated in different cell types and in ex vivo organ cultures of mucosal explants of healthy donors and Crohn's disease (CD) patients. The extract showed effect in both colitis models reducing the expression of proinflammatory mediators (IL‐1β, TNF‐α, and iNOS), and improving the intestinal epithelial barrier integrity restoring the expression of ZO‐1, MUC‐2, and TFF‐3. These effects were confirmed in vitro. Furthermore, it reduced the production of proinflammatory mediators (IL‐1β, IL‐6, IL‐8, and TNF‐α) in intestinal mucosal samples from CD patients. Conclusion: Olive leaf extract presented intestinal anti‐inflammatory activity in colitis mouse models, maybe be related to its immunomodulatory properties and the capacity to restore the intestinal epithelial barrier. Besides, the extract could also regulate the activity of cells involved in the inflammatory response. Abstract : The intestinal anti‐inflammatory effects of an olive leaf extract was evaluated in different experimental models of colitis in mice. Additional assays were performed to test the in vitro immunomodulatory activity of the extract in different cell types actively involved in the intestinal immune response (RAW 264, CMT‐93, and Caco‐2 cells), in peripheral blood mononuclear cells as well as in colonic biopsy specimens obtained from healthy and Crohn's disease patients.